The Influence of Internal Communication in the Organization on PT Wahyu Abadi (CIKARANG) Employee Performance - Fauzobihi, Fauzobihi; Tarziyah, Indina; Partimah, Partimah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
PT Wahyu Abadi is a company operating in the manufacturing industry specializing in printing and packaging. The company seeks to push the printing and packaging industry to new levels of innovation. This company provides business solutions in the fields of printing, packaging, digital and supply chain. PT Wahyu Abadi was chosen as the research location, which is located on Jl. Angsana Raya Blok L1 No 17, Delta Silicon 1 Industrial Area, Lippo Cikarang Bekasi, Indonesia. The analysis carried out using SPSS 21.0 found that the value of the influence of Internal Communication (X) on Employee Performance (Y) can be narrated using the regression formula Y= a+bX, so the regression value resulting from the calculation above is Y = 55.517 + 0.151X. The constant value (a) is = 55.517 while the coefficient value (b) = 0.151. The meaning of this equation is that if there is no internal communication, the employee's performance will be worth 55,517 units. However, if there is an increase of one unit/unit of the internal communication variable, it will be affected by an increase in employee performance by 0.515. Thus the t table: if the error level α = 5% (0.05%) and the two-sided test df = n – 2 (33 – 2 = 31), then the t table value is 2.040 and based on the calculation above the t count is obtained equal to 0.742 < t table 2.040, then it can be concluded that H_0 is accepted and H_a is rejected because the calculated t is smaller than the t table. Thus it can be concluded that internal communication variables do not influence employee performance variables at PT Wahyu Abadi